THE FUTURE OF CONSTITUTIONAL GOVERNANCE IN PAKISTAN: PROSPECTS AND CHALLENGES - Jafar Nazir; Zahida Jabeen; Saqib Ullah Khan (Journal of Religion and Society, 2024)
This article critically examines the prospects and challenges facing constitutional governance in Pakistan, focusing on the evolving dynamics that influence its legal and political framework. As Pakistan navigates through a complex matrix of political instability, military influence, and judicial activism, the integrity and efficacy of its constitution are continually tested. The study explores key factors that will shape the future of constitutional governance in Pakistan, including legal reforms, the role of civil society, and the balance of power among the branches of government. The analysis begins with an overview of Pakistan's constitutional history, highlighting the frequent amendments and interruptions by military coups that have undermined democratic governance. It discusses recent efforts towards constitutional reform, which aim to strengthen democratic institutions and ensure greater judicial independence. The role of the Supreme Court in asserting its authority over other branches of government, often stepping into political domains through judicial activism, is also critically evaluated. Furthermore, the article addresses the ongoing challenges such as political corruption, lack of transparency, and the influence of external powers on domestic policies. These issues pose significant obstacles to the constitutional mandate of democracy and rule of law. The paper also considers the impact of regional instability and internal security issues, which have historically justified the extension of military authority at the expense of civilian rule. In conclusion, "The Future of Constitutional Governance in Pakistan: Prospects and Challenges" provides insights into the ongoing struggle for a stable and effective constitutional governance system in Pakistan. It offers recommendations for fostering a balanced power distribution, enhancing legal education, and promoting civic engagement as essential steps towards sustainable constitutional governance. Keywords: Pakistan, constitutional governance, legal reforms, judicial activism, democratic institutions, military influence, rule of law, political stability, civic engagement, regional instability.